1994
DOI: 10.1113/jphysiol.1994.sp020289
|View full text |Cite
|
Sign up to set email alerts
|

GABA receptor mediation of median preoptic nucleus‐evoked inhibition of supraoptic neurosecretory neurones in rat.

Abstract: 1. This study evaluated the influence of focal electrical and chemical microstimulation in the median preoptic nucleus (MnPO) on the excitability of putative vasopressin and oxytocin neurones recorded in the supraoptic nucleus of urethane-or pentobarbitoneanaesthetized rats. with the first few impulses but this was then replaced by suppression of activity; another ten cells displayed excitation alone, and eight cells demonstrated only suppression. The depressant responses evoked during trains of MnPO stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 35 publications
1
33
0
Order By: Relevance
“…MnPO relays the information from the OVLT to the magnocellular neurosecretory cells in the SON. Though a recent electrophysiological study (33 ) showed that GABAergic inhibitory neurones in the MnPO project to the SON, most SON neurones were excited by electrical stimulation of the MnPO in our previous study (15). And moreover, in the present study the MnPO neurones projecting to the SON area responded to haemodynamic or osmotic stimuli in the same manner as the SON neurones did ( 15); i.e.…”
Section: Discussionsupporting
confidence: 58%
“…MnPO relays the information from the OVLT to the magnocellular neurosecretory cells in the SON. Though a recent electrophysiological study (33 ) showed that GABAergic inhibitory neurones in the MnPO project to the SON, most SON neurones were excited by electrical stimulation of the MnPO in our previous study (15). And moreover, in the present study the MnPO neurones projecting to the SON area responded to haemodynamic or osmotic stimuli in the same manner as the SON neurones did ( 15); i.e.…”
Section: Discussionsupporting
confidence: 58%
“…In an earlier in vivo analysis, we reported that stimulation in MnPO evoked GABA A -mediated inhibition in target neurons in the supraoptic nucleus (27), implying that at least this output of MnPO was inhibitory in nature. Consistent with this notion are Fig.…”
Section: Perspectivesmentioning
confidence: 98%
“…Indeed, 20-30% of neurons in the MnPO are warm sensitive and have been proposed to play an important role in thermoregulation, including nonshivering thermogenesis (71). Efferent projections from the MnPO tend to be inhibitory (44), which is consistent with their GABAergic nature (43). Furthermore, MnPO neurons that project to the midbrain periaqueductal gray matter (which contains neurons generating excitatory signals for nonshivering thermogenesis) are activated by heat exposure (75), thus confirming their inhibitory role in the control of thermogenesis.…”
Section: Hyperthermia Induced By Ovlt Lesionmentioning
confidence: 99%